Implementation of Inclusive Education Based on Religious Moderation: A Case Study at PAUD Joglo Rumah Damai Peace Place Pati - Asfar, Khalimatus Sa’diyah; Parawati, Erina Dwi (Universitas Negeri Semarang, 2025)
Inclusive education based on religious moderation is an important solution in forming a tolerant generation that values ​​diversity from an early age, especially in Indonesia which has a pluralistic society. This study aims to analyze the implementation of inclusive education based on religious moderation at PAUD Joglo Rumah Damai Peace Place Pati, with a focus on pedagogical strategies, obstacles, and their impact on student development. The research method uses a qualitative case study approach through observation, interviews, and document analysis, with data analysis following the Miles and Huberman model. The results of the study indicate that a holistic approach through a flexible curriculum, game-based methods, and collaboration with parents has succeeded in creating an inclusive environment that supports empathy, tolerance, and students' social skills. The main obstacle in the form of parental inconsistency is overcome through intensive communication and mentoring. The conclusion of this study confirms that the integration of the principles of inclusivity and religious moderation is effective in building children's character that values ​​diversity.